Absorbed dose threshold for single-layer ZrO2, HfO2, and Al2O3 dielectric coatings at 355 nm - Atkočaitis, Erikas; Melninkaitis, Andrius (Optics letters, 2025)
This study investigates ultraviolet laser-induced fatigue and absorptance dynamics in single-layer Al2O3, HfO2, and ZrO2 dielectric coatings on fused silica substrates using 355 nm, 10 ps pulses at a repetition rate of 1 MHz. Laser-induced damage threshold testing, combined with photothermal common-path interferometry, reveals that the formation of the "color change" damage is a multistage, cumulative process, dependent on material treatment and laser intensity. These findings offer insights into optical fatigue mechanisms and provide a pathway for non-catastrophic lifetime assessment of optical coatings based on the accumulation threshold of the absorbed dose.This study investigates ultraviolet laser-induced fatigue and absorptance dynamics in single-layer Al2O3, HfO2, and ZrO2 dielectric coatings on fused silica substrates using 355 nm, 10 ps pulses at a repetition rate of 1 MHz. Laser-induced damage threshold testing, combined with photothermal common-path interferometry, reveals that the formation of the "color change" damage is a multistage, cumulative process, dependent on material treatment and laser intensity. These findings offer insights into optical fatigue mechanisms and provide a pathway for non-catastrophic lifetime assessment of optical coatings based on the accumulation threshold of the absorbed dose.